Undergraduate engineering students’ beliefs about their own intelligence - Adams, Allison (Kansas State University, 2021)
This research endeavored to provide insight on the development of undergraduate engineering students’ beliefs about their own intelligence. Carol Dweck’s Mindset framework was used as the foundation. Mindset describes how fixed and growth mindsets can affect success. A fixed mindset individual believes that their traits are unchanging, while a growth mindset individual believes their traits can change and grow through effort. Prior research has found that the belief that one’s traits can change typically leads to valuing criticism and effort, responding positively to challenges, seeking to improve upon past failures, and becoming more persistent than does the belief that traits are static. The researcher developed, piloted, and refined an interview protocol and conducted interviews on undergraduate engineering students. The transcripts were initially analyzed with Attitude, Value, and Belief coding as described in the Coding Manual for Qualitative Researchers by Saldaña and a codebook was begun. Mindset and Attitude, Value, and Belief coding was found to be insufficient to adequately understand the beliefs of the students because they were focused on the individual. It was necessary to find a means to link the individuals with the engineering culture they lived in, were shaped by, and contributed to. To this end, the focus was shifted to the themes of Judgement, Effort, and Motivation. It was discovered that students were influenced by a variety of motivations, both internal and external. They tended to associate effort with the time spent on a task more than with the difficulty of the task. The students also felt pressure to find a correct amount of time spent on engineering school. Too little effort was a sign that the students were too lazy to be engineers, while too much was a sign that they were not smart enough to be engineers. Their images of themselves were influenced by their motivations and their views of effort as well as their views of their peers and the judgements they perceived themselves to receive from others. This thesis details the process of creating an interview protocol, conducting interviews, coding, and discovering these themes, as well as the findings resulting from them.
Keywords: Undergraduate engineering students; Mindset; Beliefs about intelligence; Beliefs about effort; Students' motivations